Plasma Assisted Cooling of Hot Surfaces on Hypersonic Vehicles - Hanquist, Kyle M.; Boyd, Iain D. (Frontiers in Physics, 2019)
Electron transpiration cooling (ETC) is a proposed thermal management approach for the leading edges of hypersonic vehicles that utilizes thermionic emission to emit electrons to carry heat away from the surface. A modeling approach for assessing ETC in a computational fluid dynamics (CFD) framework and is evaluated using previously completed experiments. The modeling approach is presented includes developing boundary conditions to account for space-charge-limited emission to accurately determine the level of electron emission from the surface. The effectiveness of ETC for multiple test cases are investigated including sharp leading edges and blunt bodies. For each of these test cases, ETC affects the surface properties, most notably the surface temperature, suggesting that ETC occurs for bodies in thermally intense, ionized flows, no matter the shape of the leading edge. An approximate approach is also presented to assess ETC in an ionized flow and compares its cooling power to radiative cooling.